Emotional: Exploitation & Burnout in Creator Culture - Thorne, Sarah (CLCWeb : Comparative literature and culture, 2022)
In recent years, a growing list of content creators have published videos announcing that they are leaving YouTube, taking a break, or reducing their upload schedule (Alexander). Many of these young creators state that their decision resulted from burnout, caused by a relentless schedule and obsession with YouTube's algorithm and analytics--tools essential to success on this highly competitive creative platform (Srnicek). Its opaque algorithm, however, induces anxiety; an affect described as that which "arises when the subject is confronted by the desire of the Other and does not know what object he is for that desire" (Evans 12). Here, the Other is conflated as both audience and algorithm, insofar as what videos trend or are recommended is a complex merging of user-engagement and vetting by the algorithm. Attempting to discover the desire of the Other, creators examine data to speculate about what content will gain the most views. While some creators opt to chase trends and use clickbait titles, others avoid the algorithm's detection and suppression by omitting key words known to be flagged, while others embrace defeat and instead drive their channels using drama and negative affect (Berryman and Kavka). Drawing on Lacan's psychoanalytic clinical structures and theory of anxiety, this article examines how each of these approaches to navigating the platform represents a neurotic and sometimes perverse response to the algorithmic Other that is influenced by a neoliberal notion of creativity that privileges growth over its socially transformative power (Mould).